Efektivitas Penerapan Sistem Keuangan Desa (SISKEUDES) Dalam Meningkatkan Akuntabilitas Dan Transparansi Laporan Keuangan Desa (Studi Kasus Desa Gelogor, Desa Ombe Baru dan Desa Rumak Kecamatan Kediri) - Aldy Irwansyach; Rr. Sri Pancawati Martiningsih (Fakultas Ekonomi dan Bisnis Unram, 2026)
This study describes the effectiveness of implementing the Village Financial System (SISKEUDES) and its impact on the accountability and transparency of financial reports in Gelogor, Ombe Baru, and Rumak villages (Kediri District, West Lombok). Using a qualitative descriptive method, data were collected through interviews, observations, and documentation with 13 selected and community village officials, and then analyzed using the Miles & Huberman model. The results indicate that the implementation of SISKEUDES in Gelogor and Rumak villages has been effective. The system has successfully enhanced the accountability of financial reports as they are prepared in a timely manner, comply with the format of the Ministry of Home Affairs Regulation (Permendagri) No. 20 of 2018, and are supported by complete documentation. However, transparency is not yet optimal due to the community's lack of understanding regarding technical formats. The main obstacles identified in the research include network infrastructure issues and a lack of training, while the commitment of village leaders serves as a key supporting factor. It is recommended to provide routine training for village officials, improve infrastructure, and simplify the reporting format to make it more accessible and easier for the community to understand.